Uji Aktivitas Antioksidan Kombinasi Infusa Daun Sirih (Piper betle L), Ekstrak Etanolik Tanaman Bundung (Actinuscirpus grossus) dan Kulit Jeruk Nipis (Citrus aurantifolia) - Kunti Nastiti; Noval Noval; Darini Kurniawati (Jurnal Surya Medika (JSM), 2021)
Piper betle L., the leaf, is the most often used for treatment and has been scientifically proven to have antibacterial activity. Actinuscirpus grossus plants are commonly found in Kalimantan and have antimicrobial properties. Citrus aurantifolia peel has antioxidant effects and nutritious chemical compounds in medicine. The purpose of this study was to determine the effect of antioxidant activity in a combination of Piper betle L., leaf infusion, ethanolic extract of Actinuscirpus grossus plant, and Citrus aurantifolia peel. The research method was experimental by making Piper betle L. leaves infused with water solvent. Simplisia powder of Actinuscirpus grossus plants and Citrus aurantifolia peel extracted by maceration with 95% ethanol solvent. The combination of the three plants was then tested for antioxidants by the DPPH method. Quercetin is used as a positive control. The results showed that the combination of the three plants had moderate antioxidant activity (IC50 128 ppm), but the antioxidant activity was smaller than quercetin (IC50 16.88 ppm). The combination of Piper betle L., leaf infusion, ethanolic extract of Actinuscirpus grossus plant, and Citrus aurantifolia peel has a moderate antioxidant category.